2005
DOI: 10.1111/j.1745-7254.2005.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of some benproperine metabolites in humans and investigation of their antitussive effect1

Abstract: Aim: To identify 4 unknown metabolites of benproperine (BPP, 1) in human urine after a po dose, and to investigate the antitussive effect of monohydroxylate metabolites. Methods: The putative metabolite references were prepared using chemical synthesis. Their structures were identified using 1H and 13C nuclear magnetic resonance, and mass spectrometry. The metabolites in human urine were separated and assayed using liquid chromatography‐ion trap mass spectrometry (LC/MS/MS), and further confirmed by compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The electrospray ionisation (ESI), a soft ionization technique, increases the possibility of analyzing high labile and polar phase II metabolites at trace levels [14][15][16]. Therefore, LC-MS-MS is a more powerful analytical tool for the identification of drug metabolites in biological matrices by comparing the changes in molecular masses ( M), retention times and MS 2 spectral patterns of metabolites with those of parent drug [17,18], even if the standard of metabolites were not obtained [19,20], or the metabolites are not achieved a good chromatographic resolution [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The electrospray ionisation (ESI), a soft ionization technique, increases the possibility of analyzing high labile and polar phase II metabolites at trace levels [14][15][16]. Therefore, LC-MS-MS is a more powerful analytical tool for the identification of drug metabolites in biological matrices by comparing the changes in molecular masses ( M), retention times and MS 2 spectral patterns of metabolites with those of parent drug [17,18], even if the standard of metabolites were not obtained [19,20], or the metabolites are not achieved a good chromatographic resolution [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of its unrivaled speed, sensitivity, and low sample consumption, ESI-MS has become a powerful tool to probe the interactions of the protein hosts and the guests, including inhibitors, cofactors, metal ions, and nucleic acids. Furthermore, it can offer stoichiometric information of the complex directly and identify multiple components simultaneously, thus dramatic numbers of research articles have been reported [8][9][10][11][12][13] . For instance, Bligh et al [14] measured the dissociation constants of inhibitors non-covalently binding to the Src homology 2 (Src SH2) domain through non-linear regression curve fitting.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 provides an overview of many APIs included in dietary supplement products from 2017 through 2021, including whether they are included in FDA-approved products, known adverse events, and drug interactions. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Including APIs in dietary supplements is much riskier than when they are included in FDA-approved finished pharmaceutical products. FDA-approved finished pharmaceutical products have consistent doses, manufacturing processes, pharmacokinetics, and formulations.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Several of the APIs included in dietary supplements have never been reviewed by the FDA, so the true balance of benefits to harms cannot be determined even when they are being used alone. 10,15 Others were specifically turned down for FDA approval or removed from the US market because the balance of benefits to harms in products were known to be unfavorable. 9,12,13 It is unconscionable that sibutramine and phenolphthalein are still being included in dietary supplements for weight loss after they were removed from the US market by the FDA for valid safety concerns.…”
Section: Discussionmentioning
confidence: 99%